Reviews of Christopher Reed, The Chrysanthème Papers: The Pink Notebook of Madame Chrysanthème and Other Documents of French Japonisme (2010) and Josephine Lee, The Japan of Pure Invention: Gilbert & Sullivan’s The Mikado (2010) - Morris, Narrelle (Taylor & Francis, 2012)
BOOK REVIEW